Protective effect of extract of the Camellia japonica L. on cerebral ischemia-reperfusion injury in rats - Weizhuo Lu; Ling Xv; Jiyue Wen (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: We investigated the protective effect of the extract of the Camellia japonica L. flower on cerebral ischemia-reperfusion injury in rats. Methods: The rat ischemia-reperfusion injury was induced by middle cerebral artery occlusion for 90 minutes and reperfusion for 48 hours. The animals received an intravenous injection once a day of 20, 40, 80 mg/kg extract of C. japonica for three consecutive days before the ischemia reperfusion. The learning and memory function, the infarct volume, serum malondialdehyde (MDA) level and lactate dehydrogenase activity, and extravasation of immunoglobulin G (IgG) into cerebral parenchyma were assessed as the cell damage index. Results: Pretreatment with extract of C. japonica markedly reduced the infarct volume, serum malondialdehyde level and lactate dehydrogenase activity, and markedly inhibited the extravasation of IgG. Moreover, pretreatment with extract of C. japonica may also inhibit the learning and memory deficits induced by an ischemia-reperfusion injury. Conclusion: It was concluded that pretreatment with extract of C. japonica has a protective effect on cerebral ischemia-reperfusion injury in rats.